Fenomena Penggunaan Bahasa Jaksel (Code-switching Language) dalam Komunikasi Interpersonal Siswa di SMA Negeri 11 Medan - Yudi Setiawan (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
This research aims to know the Jaksel Language usage phenomenon (code-switching language) in the interpersonal communication of students at SMA Negeri 11 Medan. This research uses the qualitative method with a phenomenological approach.. The result of this research is that students of SMA Negeri 11 Medan have used The Jaksel Language (code-switching) when they communicate with their friends, either directly or indirectly (via chat applications). Most of the informants used The Jaksel Language because it was their own will, some of them because of FOMO (Fear of Missing Out), and to be look cool. The six informants in this research are the members of the EL-ENC (English Eleven Club) at their school. All informants are accustomed using English for academic and non-academic purposes.